Handbook of nuclear engineering [5 vol. set] - Cacuci, Dan Gabriel [ed.] (New York Springer, 2010)
The Handbook of Nuclear Engineering is an authoritative compilation of information regarding methods and data used in all phases of nuclear engineering. Addressing nuclear engineers and scientists at all academic levels, this five volume set provides the latest findings in nuclear data and experimental techniques, reactor physics, kinetics, dynamics and control. Readers will also find a detailed description of data assimilation, model validation and calibration, sensitivity and uncertainty analysis, fuel management and cycles, nuclear reactor types and radiation shielding. A discussion of radioactive waste disposal, safeguards and non-proliferation, and fuel processing with partitioning and transmutation is also included. As nuclear technology becomes an important resource of non-polluting sustainable energy in the future, The Handbook of Nuclear Engineering is an excellent reference for practicing engineers, researchers and professionals.
Contents: v.1. Nuclear engineering fundamentals -- v.2.Reactor design -- v.3.Reactor analysis --v.4. reactors of generations III and IV -- v.5. Fuel cycles, decommissioning, waste disposal and safeguargs
Keywords: Nuclear engineering